Medical students’ unprofessional behavior and educators’ support - Ryoko Igarashi (Korean Journal of Medical Education)
In recent years, professionalism education has been incorporated into medical education as an important part of the curriculum. Through receiving professionalism education, most medical students gradually acquire professionalism, including a professional attitude. However, some medical students demonstrate unprofessional behavior that raises concerns among faculty and other students. There are various stages to dealing with unprofessional behavior, as follows: definition, prevention, detection, evaluation, correction, and follow-up. However, it is often difficult to identify unprofessional behavior and respond appropriately. In this study, overview of medical students’ unprofessional behavior from previous studies on medical students’ unprofessionalism behavior, and how to identify and evaluate medical students’ unprofessional behavior, and effective education that can correct medical students’ unprofessional behavior was analyzed by reviewing 52 articles. Medical students’ unprofessional behavior is classified into the following four categories: “lack of involvement,” “lack of integrity,” “lack of interaction,” and “lack of introspection.” The occurrence of unprofessional behavior was found to be attributed to personal problems, interpersonal problems, external factors, and environmental factors. Educators analyzed unprofessional behavior and its causes from four categories. Medical students should perform reflective writing to help them reflect on their unprofessional behavior. Educators should use this reflective writing to interact with medical students, and to investigate and analyze the students’ unprofessional behavior. Furthermore, educators will need to assess unprofessional behavior using a roadmap to address unprofessionalism, and to respond appropriately to each stage of the roadmap. Individualized educational interventions should be provided to help students correct their unprofessional behavior.